2020
DOI: 10.7759/cureus.10653
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Intracranial Hemorrhage After Minor Head Injury

Abstract: Introduction: Computed tomography scans of the head (CTH) are an important component of the initial patient evaluation after blunt head trauma in select patients. Here we review findings of CTH performed for mild traumatic brain injury (TBI) at a Level I trauma center over a two-year period. We subsequently discuss the role and limitations of published clinical decision rules aiming to decrease unnecessary CTH in mild TBI patients. Methods: We reviewed all Emergency Department CTH obtained after blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(41 reference statements)
1
4
1
Order By: Relevance
“…A study by Roghani and Ali showed 3% SAH, 10% SH, and 10% EH (10). A study conducted by Bonney et al in 2020 showed that the most common findings of intracranial hemorrhages were 4.7% for subdural hemorrhage, 4.5% for traumatic subarachnoid hemorrhage, and 3.8% for intraparenchymal hemorrhage (14). However, the current study revealed that subdural hemorrhage accounted for 36% of all intracranial hemorrhages, followed by epidural hemorrhages (28%), subarachnoid hemorrhages (20%), and intraparenchymal hemorrhages (16%).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…A study by Roghani and Ali showed 3% SAH, 10% SH, and 10% EH (10). A study conducted by Bonney et al in 2020 showed that the most common findings of intracranial hemorrhages were 4.7% for subdural hemorrhage, 4.5% for traumatic subarachnoid hemorrhage, and 3.8% for intraparenchymal hemorrhage (14). However, the current study revealed that subdural hemorrhage accounted for 36% of all intracranial hemorrhages, followed by epidural hemorrhages (28%), subarachnoid hemorrhages (20%), and intraparenchymal hemorrhages (16%).…”
Section: Discussioncontrasting
confidence: 65%
“…Additionally, unrecognized intracranial hematoma continues to have significant clinical and legal ramifications for emergency medicine practitioners (12). This last factor is likely responsible for the growing use of CTH because no decision tool has ever demonstrated 100% sensitivity across a population tested (14).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hematomas vanished and the microvasculature morphology remodeled within 48 h, indicating a microvascular recovery process (Lin et al, 2022). Two recent reviews showed that 12.9%–17.3% of mTBI patients suffer intracranial hemorrhage (Bonney et al, 2020; Isokuortti et al, 2018). Relative to those with a single mTBI, rmTBI demonstrates an increased prevalence of cerebral microhemorrhages in football players (Slobounov et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported on hemorrhage detection using CT scans ( 9 , 19 ) and these efforts used considerably larger sample sizes than the external CT cases for the current VIOLA-AI tool. It is intriguing that the VIOLA-AI tool achieved adequate classification performance for all samples, but the scores decreased when considering the low yield cases of consecutive mild TBI cases ( 29 ). This suggests that VIOLA-AI is currently better suited for ICH and confirmed TBI-bleeds rather than as a detection tool for mild TBI sites.…”
Section: Discussionmentioning
confidence: 99%